Antibiotic prescribing pattern in different clinical departments at Kathmandu Medical College Teaching Hospital - Dixit, Sanjaya Mani; Shrestha, Binaya (Journal of Kathmandu Medical College, 2018)
Background: Antibiotics have transformed the practice of medicine for good; by making once lethal infections treatable. However, antimicrobials have been overused both in prophylaxis and therapy. Patients unnecessarily exposed to antibiotics are at risk for serious adverse events while increasing the chances of antimicrobial resistance. Patients with infections caused by drug-resistant bacteria are at increased risk of worse clinical outcomes and even death. It is therefore imperative to use our arsenal of antibiotics wisely.Objectives: A prospective cross sectional study was carried out with the aim of identifying prescription pattern of antibiotics in different medical units at Kathmandu Medical College Teaching Hospital, Sinamangal. Investigating the prescription pattern of doctors and providing them necessary feedback plays a vital role in improving the prescription quality and promoting the rational prescription pattern.Methodology: A study was carried out on in-patient prescription data collected at random from patients admitted in different clinical departments at the hospital. Information on medication use was obtained for the patients prescribed at least one antibiotic during their hospital stay. The antibiotic prescribing practices of different departments was compared by using the percentage method.Results: The antibiotics most commonly prescribed were Ceftriaxone, Amoxicillin + Cloxacillin, Azithromycin, and Cefixime among others. Ceftriaxone was found to be prescribed in 108 cases accounting 16.8% of the total antibiotic prescribed.Conclusion: The study highlights the current practice of antibiotics usage in clinical settings. Based on the current study it was concluded that Cephalosporins are the mostly used antibiotics in in-patient settings.